Thromboplasminflammation in COVID-19 Coagulopathy: Three Viewpoints for Diagnostic and Therapeutic Strategies - Gando, Satoshi; Wada, Takeshi (Frontiers in Immunology, 2021)
Thromboplasminflammation in coronavirus disease 2019 (COVID-19) consists of angiotensin II (Ang II)-induced coagulopathy, activated Factor XII (FXIIa)- and kallikrein and kinin system (KKS)-enhanced fibrinolysis, and disseminated intravascular coagulation (DIC). All three conditions induce systemic inflammation via each pathomechanism-developed production of inflammatory cytokines. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection downregulates angiotensin-converting enzyme 2, leading to an increase in Ang II levels. Ang II-induced coagulopathy comprising platelet activation, thrombin generation, plasminogen activator inhibitor-1 expression, and endothelial injury causes thrombosis via the angiotensin 1 receptor. SARS-CoV-2 RNA and neutrophil extracellular traps (NETs) DNA activate FXII, resulting in plasmin generation through FXIIa- and kallikrein-mediated plasminogen conversion to plasmin and bradykinin-induced tissue-type plasminogen activator release from the endothelium via B2 receptors. NETs induce immunothrombosis at the site of infection through histone- and DNA-mediated thrombin generation, insufficient anticoagulation controls, and inhibition of fibrinolysis. However, if the infection is sufficiently severe, immunothrombosis disseminates into the systemic circulation, and DIC, which is associated with the endothelial injury, ensues. Inflammation, and serine protease networks of coagulation and fibrinolysis, militate each other through complement pathways, which exacerbates three pathologies of COVID-19 coagulopathy. COVID-19 coagulopathy causes microvascular thrombosis and bleeding, resulting in multiple organ dysfunction and death in critically ill patients. Treatment targets for improving the prognosis of COVID-19 coagulopathy are thrombin, plasmin, and inflammation as well as SARS-CoV-2 infection. Several drugs are candidates for controlling these conditions; however, further advances are required to establish robust treatment strategies for COVID-19 coagulopathy.